Math, asked by vinnakotaharigopal, 1 year ago

solve it please as fast as you can

Attachments:

Answers

Answered by shadowsabers03
0

Consider the term,

\dfrac {a^{-1}}{a^{-1}+b^{-1}}

Well we know that x^{-1}=\dfrac {1}{x}. Thus,

\dfrac {a^{-1}}{a^{-1}+b^{-1}}=\dfrac {\left (\dfrac {1}{a}\right)}{\left (\dfrac {1}{a}+\dfrac {1}{b}\right)}\\\\\\\dfrac {a^{-1}}{a^{-1}+b^{-1}}=\dfrac {\left (\dfrac {b}{ab}\right)}{\left (\dfrac {a+b}{ab}\right)}\\\\\\\dfrac {a^{-1}}{a^{-1}+b^{-1}}=\dfrac {b}{a+b}

Similarly,

\dfrac {a^{-1}}{a^{-1}-b^{-1}}=\dfrac {\left (\dfrac {1}{a}\right)}{\left (\dfrac {1}{a}-\dfrac {1}{b}\right)}\\\\\\\dfrac {a^{-1}}{a^{-1}-b^{-1}}=\dfrac {\left (\dfrac {b}{ab}\right)}{\left (\dfrac {b-a}{ab}\right)}\\\\\\\dfrac {a^{-1}}{a^{-1}-b^{-1}}=\dfrac {b}{b-a}

Then,

\begin {aligned}&\textsf {LHS}\\\\\implies\ \ &\dfrac {a^{-1}}{a^{-1}+b^{-1}}+\dfrac {a^{-1}}{a^{-1}-b^{-1}}\\\\\implies\ \ &\dfrac {b}{a+b}+\dfrac {b}{b-a}\\\\\implies\ \ &b\left (\dfrac {1}{a+b}-\dfrac {1}{a-b}\right)\\\\\implies\ \ &b\left (\dfrac {(a-b)-(a+b)}{(a+b)(a-b)}\right)\\\\\implies\ \ &b\left (\dfrac {a-b-a-b}{a^2-b^2}\right)\\\\\implies\ \ &b\left (\dfrac {-2b}{a^2-b^2}\right)\\\\\implies\ \ &\dfrac {-\left(2b^2\right)}{a^2-b^2}\\\\\implies\ \ &\textsf {RHS}\end {aligned}

Hence Proved!

#answerwithquality

#BAL

Similar questions